Cytometric characterization of Circulating Tumor Cells Captured by microfiltration and their correlation to the cellsearch® CTC test - Adams, Daniel L.; Stefansson, Steingrimur; Haudenschild, Christian; Martin, Stuart S.; Charpentier, Monica; Chumsri, Saranya; Cristofanilli, Massimo; Tang, Cha‐Mei; Alpaugh, R. Katherine (Cytometry. Part A, 2015)
Recent studies reporting hundreds, to thousands, of circulating tumor cells (CTCs) in the blood of cancer patients have raised questions regarding the prevalence of CTCs, as enumerated by the CellSearch® CTC Test. Although CellSearch has been shown to consistently detect clinically relevant CTCs; the ability to only capture EpCAM positive cells has led to speculation that it captures limited subsets of CTCs. In contrast, alternative approaches to CTC isolation are often cited as capturing large numbers of CTCs from patient blood. Not surprisingly the number of cells isolated by alternative approaches show poor correlations when compared to CellSearch, even when accounting for EpCAM presence or absence. In an effort to address this discrepancy, we ran an exploratory method comparison study to characterize and compare the CTC subgroups captured from duplicate blood samples from 30 breast and prostate cancer patients using a microfiltration system (CellSieve™) and CellSearch. We then categorized the CellSieve Cytokeratin(CK)+/CD45−/DAPI+ cells into five morphologically distinct subpopulations for correlative analysis. Like other filtration techniques, CellSieve isolated greater numbers of CK+/CD45− cells than CellSearch. Furthermore, analysis showed low correlation between the total CK+/CD45− cells captured by these two assays, regardless of EpCAM presence. However, subgrouping of CK+/CD45−/DAPI+ cells based on distinct cytokeratin staining patterns and nuclear morphologies elucidated a subpopulation correlative to CellSearch. Using method comparison analyses, we identified a specific CTC morphology which is highly correlative between two distinct capture methods. These data suggests that although various morphologic CTCs with similar phenotypic expressions are present in the blood of cancer patients, the clinically relevant cells isolated by CellSearch can potentially be identified using non‐EpCAM dependent isolation. © 2014 The Authors. Published by Wiley Periodicals, Inc.